Exploring the impact of contingency theory on sustainable innovation in Malaysian manufacturing firms - Muhammad Fakhrul, Yusuf; Nur Anis Imalyn, Mohamad Nasarudin; Sorooshian, Shahryar; Muhammad Ashraf, Fauzi; Nur Muneerah, Kasim (MDPI, 2023)
This study looks at the impact of contingency theory on sustainable innovation in Malaysian manufacturing firms. A quantitative approach was used, with convenience sampling to select participants from a target population of Malaysian manufacturing employees. An online survey distributed via email was used to collect 101 sets of data for the study. PLS-SEM (Partial Least Squares Structural Equation Modeling) was used to analyze the collected data. According to the findings, corporate sustainable support policies and sustainable incentives have a significant positive impact on sustainable innovation in Malaysian manufacturing firms, whereas top management commitment was found to be insignificant. Companies that prioritize sustainable practices through policies and incentives are more likely to promote sustainable innovation, according to the findings. As a result, businesses should prioritize developing these two attributes in order to foster sustainable innovation, thereby improving sustainability practices and contributing to the country’s long-term development goals. Future research should, however, investigate why top management commitment may not be a significant driver of sustainable innovation in Malaysian manufacturing firms.